PENGEMBANGAN VIDEO PEMBELAJARAN PADA MATA KULIAH SHAKAI GENGOGAKU TOPIK I: VARIASI BAHASA DI JEPANG - Saputra, I Nyoman Gunawan; Adnyani, Kadek Eva Krishna; Hermawan, Gede Satya (Program Studi Sastra Jepang Fakultas Bahasa Asing Unmas Denpasar, 2022)
This study aims to: (1) Develop educational videos in the shakai gengogaku class, especially topic I: Language variations in Japan, in the Japanese language education department of Ganesha University of Education (UNDIKSHA). (2) To analyze the level of feasibility of the developed product. This study uses the Multimedia Development Life Cycle (MDLC) development model introduced by Luther, and modified by Binanto (2010). The results of this study are: (1) 2 educational videos that match the criteria of a good educational video proposed by Buchner, which are less than 6 minutes long, delivered in easy-to-understand language, and can be used as an introduction to understanding the material. (2) Based on the assessment by media experts, material experts, and the students, the developed educational video is very suitable for use in the shakai gengogaku class in the Japanese language education study department of UNDIKSHA.